THE ARCHITECTURAL METHODS OF FORMING THE CITY HOTEL TOURIST COMPLEX (Municipal economy of cities. Series: «Economy science», 2013)
Considered architectural and urban characteristics of the formation of urban tourist hotel complexes. Defined zoning and identified methods of architectural and planning organizations.